Remodeling of Global Transcription Patterns of Cryptococcus neoformans Genes Mediated by the Stress-Activated HOG Signaling Pathways - Ko, Young-Joon (American Society for Microbiology (ASM), 2009)
The ability to sense and adapt to a hostile host environment is a crucial element for virulence of pathogenic fungi, including Cryptococcus neoformans. These cellular responses are evoked by diverse signaling cascades, including the stress-activated HOG pathway. Despite previous analysis of central components of the HOG pathway, its downstream signaling network is poorly characterized in C. neoformans. Here we performed comparative transcriptome analysis with HOG signaling mutants to explore stress-regulated genes and their correlation with the HOG pathway in C. neoformans. In this study, we not only provide important insights into remodeling patterns of global gene expression for counteracting external stresses but also elucidate novel characteristics of the HOG pathway in C. neoformans. First, inhibition of the HOG pathway increases expression of ergosterol biosynthesis genes and cellular ergosterol content, conferring a striking synergistic antifungal activity with amphotericin B and providing an excellent opportunity to develop a novel therapeutic method for treatment of cryptococcosis. Second, a number of cadmium-sensitive genes are differentially regulated by the HOG pathway, and their mutation causes resistance to cadmium. Finally, we have discovered novel stress defense and HOG-dependent genes, which encode a sodium/potassium efflux pump, protein kinase, multidrug transporter system, and elements of the ubiquitin-dependent system.